PP.18.17: ALBUMINURIA IS RELATED TO TROPONIN T IN HYPERTENSIVE BLACK WOMEN. (June 2015) - Kruger, R.; Schutte, R.; Schutte, A.E.; Mels, C.M.C.; Van Rooyen, J.M.; Fourie, C.M.T.
Abstract : Objective: In hypertensives, troponin T, as a marker of cardiomyocyte damage, predicts the development of renal disease as reflected by micro- and macroalbuminuria. However, urinary albumin excretion also reflects general endothelial damage and relates to arterial stiffness, which in turn increases cardiac afterload and damage. We investigated the link between troponin T and albuminuria in black women without renal dysfunction, but in which hypertensive heart disease is common. Design and method: This sub-study included a cohort of 122 black women (mean age: 60.6 years) from the larger Prospective Urban and Rural Epidemiology study. ECG along with conventional cardiovascular assessments were performed. Biochemical analyses included urinary albumin and creatinine, and serum troponin T. We assessed renal function with estimated creatinine clearance and glomerular filtration rate (eGFR). Results: In bivariate analysis, ACR correlated positively with the Cornell-product, central systolic blood pressure, central pulse pressure, aortic pulse wave velocity and troponin T (all p < 0.05). After adjusting for age, body surface area, hypertension status and eGFR, the results remained unchanged for troponin T (r = 0.30; p = 0.010) and the Cornell-product (r = 0.27; p = 0.028). After performing a multiple regression analysis, we observed the same trends, however with a significant interaction with hypertension status (F = 14.3; p = 0.031). When repeating the same model in hypertensives only, troponin T associated with ACR (Adj. R2 = 0.48; β=0.55; p = 0.006). This was not the case for normotensives. Conclusions: Troponin T was positively associated with albuminuria in hypertensive black women. Our result indicates that albuminuria, even in normal range, is linked to adverse cardiomyocyte damage in hypertensive black women, possibly via the increased arterial stiffness – cardiac overload mechanism.